In Memory of Vladimir Vladimirovich Ignatov. On his 90th anniversary - Konnova, Svetlana A.; Fedonenko, Yulia P. (Известия Саратовского университета. Новая серия: Серия Химия. Биология. Экология)
February 13, 2025 marks the 90th anniversary of the birth of Honored Scientist of the Russian Federation, Doctor of Biological Sciences, Professor Vladimir V. Ignatov (1935–2018) – a famous scientist who made a signifi cant contribution to the development of bacteriochemistry, to the study of the molecular mechanisms of Staphylococcus aureus resistance to antibiotics, as well as to the creation of a scientifi c school for the study of the molecular mechanisms of the formation of plant-bacterial associative symbiosis of cereals with rhizosphere bacteria, the research results of which are world famous. Vladimir V. Ignatov recreated the Department of Biochemistry and Biophysics at the university in 1977, and taught at the department from 1967 to 2016. In 1980, on the initiative of the Academy of Sciences of the USSR, he participated in the creation of the Saratov Scientifi c Center, organized and headed the Institute of Biochemistry and Physiology of Plants and Microorganisms of the Academy of Sciences of the USSR (now the IBPPM RAS) for about 30 years. Vladimir V. Ignatov was the author of more than 400 publications; 50 dissertations were defended under his supervision, 10 of which were doctoral.